2006
DOI: 10.1182/blood-2006-06-026187
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment of apoptotic cells by microvascular endothelial cells induces proinflammatory responses

Abstract: IntroductionApoptosis is essential to maintain homeostasis in multicellular organisms and apoptotic cells are rapidly and effectively cleared by professional phagocytes before they undergo secondary necrosis and release their noxious cytoplasmic content into the environment. 1 Ineffective clearance of apoptotic cells contributes to disease pathogenesis. 2,3 This may be true especially for autoimmune diseases such as systemic lupus erythematosus (SLE) because apoptotic cells are thought to be a potential source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 57 publications
1
39
0
1
Order By: Relevance
“…HUVECs from ScienCell used up to passage 4 21 were cultured in EC medium containing 5% FBS, 1% EC growth supplement, and antibiotics.…”
Section: Cell Culturementioning
confidence: 99%
“…HUVECs from ScienCell used up to passage 4 21 were cultured in EC medium containing 5% FBS, 1% EC growth supplement, and antibiotics.…”
Section: Cell Culturementioning
confidence: 99%
“…Support for these findings came from other studies demonstrating the phagocytic capability of endothelial cells 54 . We could also show that endothelial cells exposed to apoptotic and necrotic cells exhibit enhanced adhesion properties for leukocytes and that isolated CEC from patients with vasculitis aggravated these effects further 53 . These effects on binding properties could be explained in part by release of IL-8 and MCP1, which serve as chemo-attractants.…”
Section: Circulating Endothelial Cells As Potential Mediators Of Diseasementioning
confidence: 64%
“…Disturbed clearance of apoptotic cells may play a role in systemic lupus erythematosus 52 . Interestingly, apoptotic and necrotic endothelial cells and their fragments are rapidly internalized by healthy endothelium 53 . Support for these findings came from other studies demonstrating the phagocytic capability of endothelial cells 54 .…”
Section: Circulating Endothelial Cells As Potential Mediators Of Diseasementioning
confidence: 99%
“…25,26 A critical role of DNA trafficking between cells has been also suggested in different clinical settings as in inflammation, in cancer and after organ transplantation. 17,18,27,28 Most recently, Ehnfors et al 29 used a rat-to-SCID mouse tumor xenotransplant system and showed that tumor DNA can be transferred in vivo by detecting rat and mouse fusion chromosomes in mouse tumor stromal cells. Such an approach could be also applicable in a hematopoietic cell xenotransplantation system (e.g.…”
mentioning
confidence: 99%
“…Apoptosis is a well-recognized source of DNA in several clinical settings, such as cancer, extensive burning, GvHD and transplantation. [15][16][17][18][19][20] Donor cells undergoing apoptosis release donor-DNA packaged into apoptotic bodies. 21 Although foreign DNA is normally cleared up, 22 the fate of the large amount of released donorderived genetic material in the transplant recipient is unknown.…”
mentioning
confidence: 99%